(untitled) (Baghdad Science Journal, 2024)
The apricot plant was washed, dried, and powdered after harvesting to produce a fine powder that was used in water treatment. created an alcoholic extract from the apricot plant using ethanol, which was then analysed using GC-MS, Fourier transform infrared spectroscopy, and ultraviolet-visible spectroscopy to identify the active components. Zinc nanoparticles were created using an alcoholic extract. FTIR, UV-Vis, SEM, EDX, and TEM are used to characterize zinc nanoparticles. Using a continuous processing procedure, zinc nanoparticles with apricot extract and powder were employed to clean polluted water. Firstly, 2 g of zinc nanoparticles were used with 20 ml of polluted water, and the results were Tetra 44% and Levo 32%; after that, we used 4 g (Tetra 100% and Levo 100%). Secondly, an apricot plant was used to treat water (Tetro 100%, Levo 100%). When apricot powder and zinc nanoparticles were compared in treatment water, apricot-zinc nanoparticles were preferred. Thirdly, we treated the water from some heavy metals (2 g after 25 min; Fe 99.50%, 88.75%, Cr 99.10%, Pb 100%, Sb 95%, Cd 95%, Cu 100%), and added 4 g of nanoFe 98.75%, 96.40%, Cr 83.40%, Pb 100%, Sb 77.50%, Cd 95.80%, and Cu 100%.